Implementation of the Seven Modes of the Design Innovation Process for Augment Skincare Advertising Video - Tri Utami; Bayu Setiawan; Mahimma Romadhona (Manunggal Halim Jaya, 2026)
The skincare industry in Indonesia is experiencing rapid growth, intensifying competition among local brands. In this environment, Skincare Augment faces significant challenges low brand awareness and suboptimal brand positioning, despite its strong Unique Selling Proposition (USP) centered on Salmon DNA content (PDRN 5000 ppm). Insufficient brand recognition has directly impacted sales, which have not met targets. Thus, a more effective advertising strategy is needed to bridge the gap between product quality and consumer perception. This study aims to design an advertising strategy that enhances consumer visibility and understanding of Skincare Augment’s product advantages, utilizing the Seven Modes of the Design Innovation Process through advertising videos. Employing a mixed-methods approach combining observation, in-depth interviews, and questionnaires distributed to 103 respondents aged 20–40 the research revealed that 78.6% of respondents were unfamiliar with Skincare Augment. The primary barrier to consumer interest was identified as a lack of education regarding the benefits of Salmon DNA. By applying the seven-stage process goal setting, understanding context and audience, formulating insights, exploring concepts, and realizing outputs this research developed a short storytelling video advertising concept tailored for social media platforms like Instagram and TikTok. The final output includes a storyboard, treatment, and an advertising video emphasizing the regenerative benefits of Salmon DNA. In conclusion, the Seven Modes method provides an effective framework for crafting persuasive, educational, and relevant advertisements. This approach has the potential to increase brand awareness and strengthen Skincare Augment’s positioning in Indonesia’s competitive skincare market.